1992
DOI: 10.1007/bf02839110
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and intermolecular proton transfer reactions in 2-phenyl substituted benzazoles

Abstract: The present review describes the salient features of inter-and intramolecular proton transfer reactions of 2-(2'-aminophenyl)-', 2-(3'-aminophenyl)-, 2-(4'-aminophenyl)-, 2-(2'-hydroxyphenyl)-, 2-(3'-hydroxyphenyl)-and 2-(4'-hydroxyphenyl)-benzimidazoles, benzoxazoles and benzothiazoles. Fluorescence quantum yield of the phototautomer produced by the intramolecular hydrogen bonding decreases on going from benzimidazole to benzoxazole to benzothiazole. This indicates that the rate of internal conversion increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The vibrational frequency observed for t-DMASIP-b (1276 cm −1 ) is close to that of DMAPIP-b and other 2-phenyl substituted benzazoles. 41 All these spectral characteristics indicate the structural similarities of t-DMASIP-b with 2-phenyl substituted benzazoles. The vibrational structure diminishes with a red shift upon increasing the polarity of the solvent.…”
Section: Photochemical and Photobiological Sciences Papermentioning
confidence: 83%
“…The vibrational frequency observed for t-DMASIP-b (1276 cm −1 ) is close to that of DMAPIP-b and other 2-phenyl substituted benzazoles. 41 All these spectral characteristics indicate the structural similarities of t-DMASIP-b with 2-phenyl substituted benzazoles. The vibrational structure diminishes with a red shift upon increasing the polarity of the solvent.…”
Section: Photochemical and Photobiological Sciences Papermentioning
confidence: 83%
“…Our laboratory has been active for nearly 2 decades in studying the acid−base properties of the heterocyclic molecules, containing either one or two basic centers . The acid−base chemistry carried out on 2-(4‘-aminophenyl, AP), 2-(4‘- N , N -dimethylamino phenyl, DMAP) benzimidazole , (BI), benzoxazole , (BO), and benzothiazole , (BT) has shown that the formation of the monocations (MCs) by protonating amino or dimethylamino (MC1) or the N− atom of the imidazole ring (MC2) in the S 0 and S 1 states and their relative proportions depend on the benza ring as well as on the polarity of the environments.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the fundamental interest in the area of heterocycles, these compounds can be used as intermediates, and fine products for drugs, , color industries, laser dyes, complex-forming agents, , redox systems for solar energy, and organized assemblies . Besides these applications, another area of interest is the study of hydrogen transfer and the prototropism with suitable substituents, for example, amino-, hydroxy-, and aminophenylbenzazoles . It has been observed that usually these prototropic equilibria are different in the excited singlet (S 1 ) state than the ground (S 0 ) state and may involve intramolecular proton transfer. , …”
Section: Introductionmentioning
confidence: 99%